2007
DOI: 10.1007/s10608-006-9114-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Aversion Among Depressed Older Adults with Obsessive Compulsive Personality Disorder

Abstract: Despite considerable research on depression in older adults, few studies have included individuals with personality disorders or have used laboratory tasks to examine behavioral correlates of depression among older adults. This study used the Bechara Gambling Task to examine the hypothesis that depressed older adults with co-morbid personality disorders (n = 59) would demonstrate greater aversion to risk, when compared with older adult controls without depression or personality disorders (n = 34). Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Along these lines, engaging in an increasing number of rewarding experiences has been shown to be sufficient in improving depression (Hopko, Lejuez, LePage, Hopko, & McNeil, 2003;Jacobson et al, 1996;Lejuez, Hopko, LePage, Hopko, & McNeil, 2001). Thus, if generalized, this risk-averse strategy may be an important factor in the maintenance of depressive experiences (Chapman et al, 2007), and successful treatments for unipolar depression may operate, at one level of analysis, by blocking avoidance of risk for punishment and providing opportunities for new learning to occur. Several limitations should be considered when interpreting the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, engaging in an increasing number of rewarding experiences has been shown to be sufficient in improving depression (Hopko, Lejuez, LePage, Hopko, & McNeil, 2003;Jacobson et al, 1996;Lejuez, Hopko, LePage, Hopko, & McNeil, 2001). Thus, if generalized, this risk-averse strategy may be an important factor in the maintenance of depressive experiences (Chapman et al, 2007), and successful treatments for unipolar depression may operate, at one level of analysis, by blocking avoidance of risk for punishment and providing opportunities for new learning to occur. Several limitations should be considered when interpreting the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosable as one of three anxious and fearful personality disorders (American Psychiatric Association 2000;2013), OCPD is a behavioral complex consisting of a core of excessive conscientiousness (Samuel and Widiger 2011) in which leisure is fully subordinated to labor (American Psychiatric Association 2000). Added to this core of conscientiousness, obsessives are closed to experiencing new ideas (Warner et al 2004), anxious and fearful (Sperry 2003), over-controlled (Shapiro 1999), guarded, contrary (Widiger and Costa 1994), rigid (American Psychiatric Association 2000;2013), risk averse (Chapman et al 2007), harm avoidant (Spinhoven et al 2009), and parsimonious (Freud 1908(Freud /1959. The extreme dissimilarities between the psychopathic and obsessive patterns emerge across the 20 items of the Hare Psychopathy Checklist (PCL-R), the preeminent self-report measure operationalizing psychopathy (Hertler 2014a).…”
Section: Personality Patterns and Life History Evolutionmentioning
confidence: 99%
“…Early on, Rosenwald (1972) showed experimentally that obsessives staked less money across gambling trials. Later, Chapman et al (2007) described obsessives as exemplars of risk aversion after their study found them to eschew games of chance when possible, avoid high stakes, and respond extremely conservatively to risk on a structured gambling task (Hertler 2014a).…”
Section: Risk Aversion and Loss Aversionmentioning
confidence: 99%
“…What the antisocial experiences as stimulation, the obsessive experiences as anxiety. Accordingly, Chapman et al (2007) describe the obsessive personality "…as an exemplar of a PD [personality disorder] that may be linked with aversion to risk." In Chapman et al's research, those with an obsessive personality organization chose to avoid high stakes games that could provide ample rewards with correspondingly ample punishments.…”
Section: Goal Attainment: Risk and Rewardmentioning
confidence: 99%
“…As demonstrated by Morey, Grilo, Zanarini and Gunderson (2004), obsessives show elevations in "stress related paranoia." Risk averse (Chapman et al, 2007) and harm avoidant (Spinhoven, et al, 2009) obsessives display focused vigilance (Shapiro, 1999) that is likely responsible for the modest correlations between obsessive and paranoid presentations (Samuels & Costa, 2012). Second, obsessives, though characteristically overcontrolled, are very occasionally violent.…”
Section: Obsessives and Antisocials As Ancient Antagonistsmentioning
confidence: 99%